Meeting sustainable aviation fuel policy targets through first generation corn biorefineries. (1st February 2023) - Batten, Rahamim; Galant, Or; Karanjikar, Mukund; Spatari, Sabrina
Graphical abstract: Highlights: Promising corn-to-aviation fuel GHG emission LCA presented. Pathway opportunity to meet sustainable aviation fuel policy targets. CCS and agricultural best management needed to mitigate induced LUC. Average fuel carbon intensity (AFCI) ranges from 5 to 36 gCO2 e/MJ fuel. Retrofitting 1st generation bio-refineries can benefit low C aviation fuel markets. Abstract: This paper investigates options to produce low carbon and renewable aviation fuel through existing commercial first generation biorefineries, which could be strategic given the rapid growth of the electric vehicle market for personal mobility. We evaluate the environmental impact of retrofitting a first generation biorefinery to produce aviation fuel through chemical process simulation. The analysis investigates the potential for reducing greenhouse gas (GHG) emissions and displacing fossil fuel (petroleum-based jet kerosene) in the aviation fuel industry through using corn feedstocks in dry grind biorefineries to convert sugars to 1, 4-dimethylcyclooctane (DMCO), which qualifies as renewable jet-A fuel blend and is infrastructure compatible. The average life cycle GHG emissions for a baseline case and a scenario with carbon capture and storage (CCS) of fermentative CO2 are 36 and 5 g CO2 e/MJ DMCO, respectively. Investment in CCS at the biorefinery and adoption of crop best management practices on farms are essential for mitigating the risks of induced land use change GHG emissions for existing corn biorefineries. DMCO as a low-carbon aviation fuel could be a strategic fuel product for retrofitting existing corn dry grind facilities. For aviation fuel supply, corn dry grind facilities could displace about 12 % of jet fuel demand in the near term, which would meet sustainable aviation fuel policy targets. We conclude that corn-to-DMCO shows promise for near-term low-carbon fuel markets in the aviation industry and as a bridge to developing biomass-based jet fuel in the future.